2019
DOI: 10.3389/fpls.2019.00984
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid Versus Artemisinin Anti-malarial Activity in Artemisia annua Whole-Leaf Extracts

Abstract: Artemisinin, a sesquiterpene lactone produced by Artemisia annua glandular secretory trichomes, is the active ingredient in the most effective treatment for uncomplicated malaria caused by Plasmodium falciparum parasites. Other metabolites in A. annua or related species, particularly flavonoids, have been proposed to either act as antimalarials on their own or act synergistically with artemisinin to enhance antimalarial activity. We identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 46 publications
3
31
0
Order By: Relevance
“…This finding is consistent with the relative difference in ART content and suggests that the in-vitro antimalarial potential of both Artemisia species was largely dependent upon ART content. A recent report corroborates the results of our study [ 34 ]. They used a different approach whereby they used an A .…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…This finding is consistent with the relative difference in ART content and suggests that the in-vitro antimalarial potential of both Artemisia species was largely dependent upon ART content. A recent report corroborates the results of our study [ 34 ]. They used a different approach whereby they used an A .…”
Section: Discussionsupporting
confidence: 94%
“…leaves for parasite treatment, e.g. hot water [20,31–34, this study] chloroform:ethanol [ 34 ], chloroform [ 33 ], dichloromethane (this study); method of parasite measurement, microscopic counting [ 32 34 ], lactate dehydrogenase [ 31 , 33 ] vs. SYBR Green assay [20,33,35, this study], etc. Unless such variables are fully controlled, the validity of any conclusion is challenging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medicinal plants, which are the basis of traditional medicine in various countries, have been investigated for their pharmacological properties and have revealed numerous significant novel phytochemicals with the potential to treat and manage diseases 10 . This includes the discovery of paclitaxel (Taxol), an anticancer drug discovered from the bark of the Himalayan Yew tree 11 ; berberine isoquinoline alkaloid an antineoplastic, antidiabetic drug found in plants belonging to Berberidaceae family 12 , and Artemisinin, an antimalaria drug derived from Artemisia annua 13 , to mention a few. In recent studies, plants and their constituents have shown significant potential as therapeutic agents for oxidative stress and include polyphenolic compounds such as resveratrol, gallic acid, catechin, quercetin, kaempferol, and several anthocyanins from grapes skin 14 .…”
mentioning
confidence: 99%
“…Similar findings were observed by Falodun et al [36] whereby the methanolic extracts gave the best anti-plasmodial activity. Alongside DMSO and chloroform solvents, methanol have over a long period been used in extraction of various anti-plasmodial compounds from plants [37]. Fig.…”
Section: Chloroquine and Quinine Analysis In The M Africana Extractsmentioning
confidence: 99%